2008
DOI: 10.1074/jbc.m703630200
|View full text |Cite
|
Sign up to set email alerts
|

The Rsp5 E3 Ligase Mediates Turnover of Low Affinity Phosphate Transporters in Saccharomyces cerevisiae

Abstract: In an effort to identify novel components of the PHO regulon in Saccharomyces cerevisiae, we have isolated and characterized suppressors of the Pho ؊ phenotype associated with deletion of the Pho4 transcriptional activator. Here we report that either a defective form of the Rsp5 E3 ubiquitin ligase or deletion of the End3 component of the endocytic pathway restores growth of the pho4⌬ mutant in the presence of limiting inorganic phosphate (P i ). The spa1-1 suppressor allele of RSP5 encodes a phenylalanine-to-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…When phosphate is plentiful, Pho84 is removed from the plasma membrane and targeted to the vacuole for degradation (Lagerstedt et al 2002). Similarly, Pho91 and another low-affinity phosphate transporter, Pho87, are targeted for endocytosis and vacuolar degradation by ubiquitination (Estrella et al 2008). As our synthetic grape juice medium was not limiting for phosphate, we speculate that unnecessary phosphate transport expression and recycling may actually confer a fitness disadvantage under these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…When phosphate is plentiful, Pho84 is removed from the plasma membrane and targeted to the vacuole for degradation (Lagerstedt et al 2002). Similarly, Pho91 and another low-affinity phosphate transporter, Pho87, are targeted for endocytosis and vacuolar degradation by ubiquitination (Estrella et al 2008). As our synthetic grape juice medium was not limiting for phosphate, we speculate that unnecessary phosphate transport expression and recycling may actually confer a fitness disadvantage under these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…5, Glc is ϪUra medium containing 4% glucose, whereas Gal medium is ϪUra medium containing 2% galactose and 0.1% raffinose. High-and low-P i media contain potassium phosphate at a final concentration of either 1 mM or 5 M, respectively, prepared as described previously (11). Growth media for liquid ␤-galactosidase activities are described below; solid X-Gal (5-bromo-4-chloro-3-indolyl-␤-D-galactopyranoside) indicator medium was prepared as described online (biochemistry.ucsf.edu/labs/herskowitz/ xgalagar.html).…”
Section: Methodsmentioning
confidence: 99%
“…However, independently of the conditions tested, the vacuolar targeting of both Pho87 and Pho90 strictly required the presence of their N-terminal SPX domain. Moreover, another study performed by Estrella et al (2008) [47] also showed that Pho87 and Pho91, in response to Pi deficiency, were ubiquitinated in an E3 ubiquitin ligase Rsp5-dependent manner before being targeted for endocytosis and degraded in the vacuole [47]. Consequently, in order to shed further light on the mechanisms regulating the activity of Pho87, Pho90 and Pho91, a key step would be the complete identification of the mechanisms involved in the vacuolar targeting of Pho87 and Pho90, identifying their interacting partner proteins as well as defining the key role of the SPX domain in these processes.…”
Section: The Pi Transporters: Pho87 Pho90 and Pho91mentioning
confidence: 99%